Confirmation of mutation landscape of NF1‐associated malignant peripheral nerve sheath tumors. Issue 5 (7th March 2017) - Sohier, Pierre; Luscan, Armelle; Lloyd, Angharad; Ashelford, Kevin; Laurendeau, Ingrid; Briand‐Suleau, Audrey; Vidaud, Dominique; Ortonne, Nicolas; Pasmant, Eric; Upadhyaya, Meena
Abstract: The commonest tumors associated with neurofibromatosis type 1 (NF1) are benign peripheral nerve sheath tumors, called neurofibromas. Malignant transformation of neurofibromas into aggressive MPNSTs may occur with a poor patient prognosis. A cooperative role of SUZ12 or EED inactivation, along with NF1, TP53, and CDKN2A loss‐of‐function, has been proposed to drive progression to MPNSTs. An exome sequencing analysis of eight MPNSTs, one plexiform neurofibroma, and seven cutaneous neurofibromas was undertaken. Biallelic inactivation of the NF1 gene was observed in the plexiform neurofibroma and the MPNSTs, underlining that somatic biallelic NF1 inactivation is likely to be the initiating event for plexiform neurofibroma genesis, although it is unlikely to be sufficient for the subsequent MPNST development. The majority (5/8) of MPNSTs in our analyses demonstrated homozygous or heterozygous deletions of CDKN2A, which may represent an early event following NF1 LOH in the malignant transformation of Schwann cells from plexiform neurofibroma to MPNST. Biallelic somatic alterations of SUZ12 was also found in 4/8 MPNSTs. EED biallelic alterations were detected in 2 of the other four MPNSTs, with one tumor having a homozygous EED deletion. A missense mutation in the chromatin regulator KDM2B was also identified in one MPNST. No TP53 point mutations were found in this study, confirming previous data that TP53 mutations may be relatively rare in NF1‐associated MPNSTs. Our study confirms the frequent biallelic inactivation of PRC2 subunits SUZ12 and EED in MPNSTs, and suggests the implication of KDM2B .